A decoupler assisted optimised controller design for the greenhouse system. (23rd August 2022) - Gandhi, Shriji V.; Gandhi, Ravi V.; Kakad, Santosh; Thakker, Manish
This paper presents the novelty of the feedback feed-forward linearisation integrated with the optimised PID controller for the greenhouse system (GHS). The GHS is a group of multi-input multi-output (MIMO) systems with highly coupled, disturbed, and nonlinear dynamics. Using the proposed novel approach, initially, the nonlinear MIMO system is decoupled into two independent linearised single-input single-output (SISO) systems (i.e., temperature loop and humidity loop). After the decoupling, the separated loops are regulated by the genetic algorithm-based optimised PID controllers. The extensive simulation study is carried out for the stabilising and the tracking control for both the loops of the GHS in the presence of various initial conditions, and various load disturbances (e.g., canopy temperature, external temperature, external humidity, and solar radiation). Finally, the performance robustness of the proposed control structure is compared with the linear quadratic regulator (LQR) controller, conventional PID controller, and the Ziegler-Nichols tuned PID controller under diversified scenarios.